Unravelling the roles of social media usage, individual well-being, and working environment on happiness at the workplace - A.Manaf, Aini Maznina; Tengku Mohd Azzman, Tengku Siti Aisha; Idid, Syed Arabi (IIUM Press, 2022)
Employee happiness at the workplace has become an increasingly popular topic among researchers and scholars in the past two decades due to the rising support over its role as one of the determinants of organisational outcomes. Despite the availability of vast literature on employees’ happiness, no conclusive findings have been established to the contributing factors that influence happiness at workplace. This study examined the factors that contribute to happiness at workplace. Three contributing factors, which are social media usage, individual well-being, and working environment were examined. A survey was conducted among 475 employees of manufacturing companies in Malaysia. The results revealed that social media usage was not a significant predictor to employees’ happiness despite their high usage in Facebook, Instagram, and YouTube. Nevertheless, individual well-being and working environment were found to become significant predictors to happiness at work. The study’s findings enrich the literature on employee happiness in organisations.